SSI effects on the inelastic displacement ratios of flag-shaped hysteretic SDOF systems. (October 2021) - Song, Liang-Long; Shi, Xin; Guo, Tong
Abstract: This paper presents a parametric study to evaluate the effects of soil-structure interaction (SSI) on the constant-strength inelastic displacement ratios ( C R ) of self-centering single-degree-of-freedom (SDOF) systems characterized by flag-shaped hysteretic behavior. The elastic homogeneous soil half-space below the foundation is simulated according to the concept of Cone model. Intensive nonlinear time-history analyses of soil-structure systems are conducted using three sets of 20 synthetic ground motions, which are matched to the design response spectra corresponding to very dense, stiff and soft soil classes. The effects of different parameters (i.e., fundamental period of the fixed-base superstructure, T fix ; strength reduction factor, R ; structure-to-soil stiffness ratio, a 0 ; aspect ratio of the superstructure, s ; secondary stiffness ratio, α ; and energy dissipation ratio of the flag-shaped model, β ) on the inelastic displacement ratios are investigated and discussed. The analysis results indicate that similar trends are generally observed in inelastic displacement spectra with different soil class conditions, and ignoring SSI underestimates the peak inelastic displacement demands of the soil-structure systems. The inelastic displacement ratios increase when the value of R or a 0 increases, while a rise in α or β leads to lower inelastic displacement ratios. It is found that aspect ratio has basically no influence on the inelastic displacement ratios for low a 0 values, while has mitigating and amplifying influence on the inelastic displacement ratios below and above a threshold period for high a 0 values.